Proposed Guidelines for Establishing Baseline for Networking Infrastructure in Campus Environment : A Case Study of Faculty Information Technology (FTM) - Wasef Mahmoud, Sa'd Mater (2004)
Baseline plays a deterministic role in providing network managers with state-of-the-art information on their networks' current performance for future capacity planning. The lack of a simplified model and/or framework for creating baseline hampers the process of capacity planning thus cause many problems for network managers. Using multi-purpose multi-design research approach, this thesis objectively proposes systematic guidelines to create baseline for further capacity planning facilitation. Proper care has been taken in assessing the baseline requirements to capture all necessary information on networking infrastructure needed to create baseline. The authenticity and validity of the proposed guidelines has been tested using a short evaluation by experts, moreover, baseline for FTM's networking infrastructure has been established by implementing our proposed guidelines. It is hoped that our proposed guidelines, by all means, provide invaluable contribution to help FTM to develop the future capacity plan and gives a direction towards future research in capacity planning.